2022
DOI: 10.3389/fnhum.2022.870350
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Large-Scale Neuronal Network in High Myopia

Abstract: AimResting state functional magnetic resonance imaging (rs-fMRI) was used to analyze changes in functional connectivity (FC) within various brain networks and functional network connectivity (FNC) among various brain regions in patients with high myopia (HM).Methodsrs-fMRI was used to scan 82 patients with HM (HM group) and 59 healthy control volunteers (HC group) matched for age, sex, and education level. Fourteen resting state networks (RSNs) were extracted, of which 11 were positive. Then, the FCs and FNCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The ICA is an advanced data-driven approach, which evaluates the whole brain data and then separate it into individual components, enabling us to conduct in-depth observational studies of brain connectivity ( van den Heuvel et al, 2009 ; Vargas et al, 2013 ). Some previous studies have already applied it to some related diseases, such as acute thyrotoxic myopathy ( Li et al, 2022 ), attention deficit and hyperactivity disorder ( Kumar et al, 2021 ), juvenile absence epilepsy ( Parsons et al, 2020 ), high myopia ( Ji et al, 2022 ), and so on. Our brains must dynamically integrate, coordinate, and respond to all internal and external stimuli so that we could feel, remember, think, and correlate with others ( Hutchison et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ICA is an advanced data-driven approach, which evaluates the whole brain data and then separate it into individual components, enabling us to conduct in-depth observational studies of brain connectivity ( van den Heuvel et al, 2009 ; Vargas et al, 2013 ). Some previous studies have already applied it to some related diseases, such as acute thyrotoxic myopathy ( Li et al, 2022 ), attention deficit and hyperactivity disorder ( Kumar et al, 2021 ), juvenile absence epilepsy ( Parsons et al, 2020 ), high myopia ( Ji et al, 2022 ), and so on. Our brains must dynamically integrate, coordinate, and respond to all internal and external stimuli so that we could feel, remember, think, and correlate with others ( Hutchison et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, patients with HM may exhibit deficits in visual, motor, and cognitive functions. 15 Zhang demonstrated that patients with HM show variations in amplitude of low-frequency fluctuations (ALFF) and DMN across different brain regions, which might signify cognitive changes associated with HM. 16 Moreover, other studies have indicated that myopia patients are nearly twice as likely to develop cognitive impairment compared to individuals with refractive errors.…”
Section: Introductionmentioning
confidence: 99%